Collective action: New guiding principles for International Climate Finance - Heiner von Lüpke; Charlotte Aebischer; Karsten Neuhoff (DIW Weekly Report, 2021)
To limit global warming to 1.5 degrees Celsius, it is necessary for industrialized countries to support developing countries financially. The channels and mechanisms under which this support would be provided are known as International Climate Finance. Building upon expert interviews with a focus on the industrial sector, this report analyses the different areas of International Climate Finance and suggests ways for increasing its efficiency. International Climate Finance currently strongly builds on traditions of development cooperation and aims at creating incentives and providing support for greenhouse gas mitigation efforts in recipient countries. This report suggests modifying International Climate Finance on the basis of Elinor Ostrom's principles of global cooperation. One of these principles is reciprocity of mitigation efforts: donor countries combine their financial support of recipient countries with domestic climate policy goals. Knowledge exchange and technical cooperation could strengthen mutual trust and increase social consciousness in donor and recipient countries. Were International Climate Finance instruments to be redesigned according to these principles, they could legitimize stronger national steps to CO2 mitigation and support an international dynamic that could accelerate the transition to climate neutrality.
Keywords: Q; 330; collective action; international climate finance; industry climate neutrality